Correlation analysis of indicators of physical condition, health and physical fitness of soldiers involved in peacekeeping operations - S.S. Fedak (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to identify the main physical qualities, which positively influence the physical state, health and military - professional career peacekeepers when performing tasks in different climatic conditions. Material : the study involved 98 military service under the contract the first age group (men). Analyzed contingent divided into groups according to climatic conditions of service: in the highlands - 37 person, in hot climates - 35 person, in towns and areas with limited space - 26 person. A correlation analysis between the results of running 100 meters, pulling, running 3 kilometre and indicators of the health and physical condition of the soldiers. Results : It was determined that the participation in peacekeeping missions in mountainous areas and in areas with a hot climate is the quality of the underlying physical endurance. With the participation in peacekeeping missions in populated areas and in areas with limited space - this is the strength and speed. Conclusions : on improving these physical qualities should focus during lessons in physical training of peacekeepers in the centers of immediate preparation for missions.